Shared Roles of Yeast Glycogen Synthase Kinase 3 Family Members in Nitrogen-Responsive Phosphorylation of Meiotic Regulator Ume6p - Xiao, Yang (American Society for Microbiology, 2000)
Nitrogen limitation activates meiosis and meiotic gene expression in yeast, but nitrogen-responsive signal transduction mechanisms that govern meiotic gene expression are poorly understood. We show here that Ume6p, a subunit of the Ume6p-Ime1p meiotic transcriptional activator, undergoes increased phosphorylation in vivo in response to nitrogen limitation. Phosphorylation depends on an N-terminal glycogen synthase kinase 3 (GSK3) target site in which substitutions cause reduced Ume6p-Ime1p interaction and meiotic gene expression, thus arguing that phosphorylation promotes functional Ume6p-Ime1p interaction. Phosphorylation of this site depends on two GSK3 homologs, Rim11p and Mck1p. Prior studies indicate that Rim11p phosphorylates both Ume6p and Ime1p in vitro and is required for Ume6p-Ime1p interaction, but no evidence has linked Mck1p function to Ume6p activity. Here we find that Mck1p-Ume6p interaction is detectable by two-hybrid assays and that meiosis in a partially defective rim11-K68R mutant is completely dependent on Mck1p. These findings argue that nitrogen limitation governs Rim11p/Mck1p-dependent phosphorylation of Ume6p, which in turn is required for Ume6p-Ime1p interaction and meiotic gene activation.